As time went by - Sanabria, José (NorthSouth Books, 2016)
"Once upon a time there was a ship that sailed beside the sun with very important people on board. The spirit of reinvention – and the importance we place on things – is beautifully expressed in José Sanabria's visually evocative story. A steamship makes a journey across time from luxury and exclusivity, industry and abandonment, to stewardship and inclusion as we see the evolving functions of the ship and the changing faces of the people who cherish it most of all."--
Keywords: Steamboats / Juvenile fiction; Wealth / Juvenile fiction; Poverty / Juvenile fiction; Steamboats / Fiction; Wealth / Fiction; Poverty / Fiction; Zeit; Wertwandel; Parabel -- Literatur; Reichtum; Gesellschaft; Armut; Dampfschiff; Leben; Glück; Familie; Bilderbuch